PENGUNGKAPAN ESG: APAKAH BERDAMPAK KE COST OF DEBT? - Johan, Joel Jedidyah; Lindrawati, Lindrawati; Susanto, Adi (Universitas Katolik Indonesia Atma Jaya, 2025)
Creditors, as a source of funding for companies, need to bear the risks inherent in the company to assess the company's ability to pay debts for the use of creditors' funds. One of the risks of concern to creditors is the risk of ESG risk consisting of Environmental (E), Social (S), and Governance (G) because this issue concerns the interests of society, such as climate change, work safety issues, as well as indications of fraud committed by the company and accompanied by government encouragement in achieving sustainability goals. The existence of ESG disclosure as a risk mitigation tool and providing additional information to reduce information asymmetry with external parties makes a company strategy to legitimize the company in the eyes of the public. Legitimacy can affect the perception of external parties, especially creditors, when deciding to determine the cost of debt as a fee for using funds that creditors have provided. The purpose of the study is to analyze the effect of ESG disclosure by using non-financial sector companies listed on the Indonesia Stock Exchange, which were analyzed using simple linear regression analysis. The results showed that ESG disclosure has a negative effect on the cost of debt. This shows that creditors in Indonesia consider disclosure of ESG information as a risk mitigation tool and can reduce information asymmetry between creditors and management as operational actors to reduce the company's cost of debt.